Gender-race intersectionality of suicide in Brazil: Analysis from 2012 to 2020 (Revista Contexto & Saúde, 2026)
Objective: the study aimed to analyze, based on gender-race intersectionality, the cases of suicide in Brazil registered in the period from 2012 to 2020. Methods: ecological, descriptive, time-series epidemiological study with data from the Death Suicide Certificates, by federation unit, in Brazil from the Mortality Information System (SIM), in the period from 2012 to 2020, from DATASUS, in the period in November 2022.  The variables marital status, education and the means used to consummate suicide and their correlation with intersectionality were analyzed. IBM SPSS software was used     Statistics    ®️ 23 for the analyses and LibreOffice Community 7.1.0.3 for graphics. Results: there was a sharper increase in suicide rates among non-white men from 2015 onwards compared to other intersectionality groups. These were mostly young, single, with low schooling and had the highest proportion of suicide cases by hanging in all years alone (p
Keywords: Intersectional framing; sexual factors; racial factors; suicide